Driving innovation from within a guide for internal entrepreneurs - Krippendorff, Kaihan (Columbia University Press, 2019)
Kaihan Krippendorff reveals how many of the modern world's most impactful creations were invented by passionate employee-innovators. He lays out a step-by-step playbook to unlock innovation from the inside, mapping the barriers that frustrate efforts to disrupt from within and providing tools to remove them